RETRACTED: Improvement of tools to assess the implementation of financial potential of corporations - Zakirova Alsou; Klychova Guzaliya; Ostaev Gamlet; Kondratiev Dmitry; Nigmetzyanov Almaz; Nikitenko Igor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001